Diagnostic Value of Pleural Effusion Mononuclear Cells Count and Adenosine Deaminase for Tuberculous Pleurisy Patients in China: A Case-Control Study - Lei, Xiaoli; Wang, Junli; Yang, Zhigang; Zhou, Shengli; Xu, Zhiwei (Frontiers in Medicine, 2019)
Background: The diagnostic value of pleural effusion mononuclear cells count for tuberculous pleurisy (TBP) is unclear. We aimed to evaluate the diagnostic value of pleural effusion mononuclear cells count and its combination with adenosine deaminase (ADA) in TBP patients. Methods: We initially analyzed 296 patients with unknown pleural effusion from the Department of Respiratory Medicine at Provincial People's Hospital during January 2014 to February 2018. Ultimately, 100 tuberculous pleurisy (TBP) patients and 105 non-tuberculous pleurisy (non-TBP) patients with pleural effusion were investigated in the current study. Meanwhile, pleural effusion mononuclear cells count and ADA test were performed to evaluate the diagnostic value for TBP. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio ( LR+), negative likelihood ratio (LR-), accuracy and area under the receiver operating characteristic (ROC) curve (AUC) of pleural effusion mononuclear cells count only and its combination with ADA for TBP diagnosis were investigated. Results: (i) The best cut-off value of pleural effusion mononuclear cells count for TBP diagnosis was 969.6 × 106/L, with the sensitivity, specificity and accuracy of 76%, 57% and 66%, respectively. (ii) Combination of pleural effusion mononuclear cells count and ADA test suggested diagnostic value for TBP. Specifically, serial test showed the sensitivity, specificity, accuracy of 65%, 90%, 78%, respectively, whereas parallel test revealed the sensitivity, specificity, accuracy of 92%, 45%, 68%, respectively. The sensitivity of parallel test (92%) was significantly higher than pleural effusion mononuclear cells count alone (76%) (X² = 23.19, p < 0.001). (iii) The area under the ROC of pleural effusion mononuclear cells count and it combined with ADA were 0.66 (95% CI, 0.59 - 0.72) and 0.83 (95% CI, 0.78 - 0.89), respectively, with statistically significant difference (Z = 3.46, p < 0.001). Conclusion: This retrospective case-control study demonstrated that pleural effusion mononuclear cells count is relatively useful for TBP diagnosis. Furthermore, the pleural effusion mononuclear cells count in combination with ADA can further improve the diagnostic accuracy of TBP.